Productivity measurements of algae using 14C-technique and oxygen technique under the influence of inorganic nitrogen sources - Lokman Shamsudin (Fakulti Pengajian Maritim dan Sains Marin, 2011)
It is felt that there is an increasing need to have a first hand knowledge on the primary productivity of the ocean as this is related to the abundance of zooplankton and other higher organisms in the marine food chain.